Implementation of the Caning Law for Non-Muslims in the Aceh Sharia Court - Siregar, Sawaluddin; Dalimunthe, Dermina (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2024)
This research was conducted to find out how the legal punishment for non-Muslims is applied in the Aceh Sharia Court based on the judge's decision. This research takes the form of field research with an empirical juridical approach. The informants used to obtain information regarding caning laws for non-Muslims were judges, everyone at the Aceh Sharia Court by conducting interviews using the purposive sampling method, documentation in the form of judge's decisions, judge's notes. In implementing Islamic law in Aceh, many obstacles were encountered, including sociological obstacles, firkah obstacles, juridical obstacles, community consolidation obstacles, formulation obstacles and political obstacles. So far, the implementation of Islamic sharia law enforcement in Aceh has always been improved. Based on findings in the field, non-Muslims who are found guilty constitutionally have the right to choose state institutions or sharia institutions to obtain justice. By choosing to go to the sharia court, the guilty person must make a letter of compliance so that caning can be applied as a sanction for the wrongdoing.